Safety and Immunogenicity of Full-Dose Trivalent Inactivated Influenza Vaccine (TIV) Compared With Half-Dose TIV Administered to Children 6 Through 35 Months of Age - Halasa, Natasha B. (J Pediatric Infect Dis Soc, 2015)
BACKGROUND: Children 6 through 35 months of age are recommended to receive half the dose of influenza vaccine compared with older children and adults. METHODS: This was a 6-site, randomized 2:1, double-blind study comparing full-dose (0.5 mL) trivalent inactivated influenza vaccine (TIV) with half-dose (0.25 mL) TIV in children 6 through 35 months of age. Children previously immunized with influenza vaccine (primed cohort) received 1 dose, and those with no previous influenza immunizations (naive cohort) received 2 doses of TIV. Local and systemic adverse events were recorded. Sera were collected before immunization and 1 month after last dose of TIV. Hemagglutination inhibition antibody testing was performed. RESULTS: Of the 243 subjects enrolled (32 primed, 211 naive), data for 232 were available for complete analysis. No significant differences in local or systemic reactions were observed. Few significant differences in immunogenicity to the 3 vaccine antigens were noted. The immune response to H1N1 was significantly higher in the full-dose group among primed subjects. In the naive cohort, the geometric mean titer for all 3 antigens after 2 doses of TIV were significantly higher in the 12 through 35 months compared with the 6 through 11 months age group. CONCLUSIONS: Our study confirms the safety of full-dose TIV given to children 6 through 35 months of age. An increase in antibody responses after full- versus half-dose TIV was not observed, except for H1N1 in the primed group. Larger studies are needed to clarify the potential for improved immunogenicity with higher vaccine doses. Recommending the same dose could simplify the production, storage, and administration of influenza vaccines.